Congenital plaque-type blue nevus on the palm of the right hand: a rare case report - Qi, Lin; Jia, Guoliang; Wang, Yanlong; Xu, Chuanjie; Yao, Chunli (Frontiers in Pediatrics, 2026)
Plaque-type blue nevus (PTBN) is a rare variant of blue nevus that mostly involves the breast, head, neck, trunk, and, rarely, the hand and palm. In this study, we report a rare case of congenital PTBN involving the right palm since birth. A 10-year-old girl presented to our department with plaque in her right palm accompanied by a tingling sensation for 1 month. Histochemical analysis indicated a heavily pigmented melanocyte proliferation in the dermis, subcutis, and fascia. The patient was diagnosed with congenital PTBN and underwent surgical excision. No recurrence was observed during a 5-year follow-up.